تأثير المالئات العضوية على منحنيات التصلب لمركبات البولي استر غير المشبع - منصور رامي; هترة علي (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف هذا البحث إلى دراسة تأثير درجة الحرارة ودرجة الحموضة PH لمالئات عضوية تمً تحضيرها من أنواع مختلفة من الأعشاب ، ودراسة نسبة المالئ على منحنيات التصلب للبولي استر غير المشبع. تظهر النتائج أن مادة بيرو كسيد البنزويل ، المستخدمة كمادة بادئة للتفاعل ، تؤثر بحدة على سلوك منحنيات التصلب، وأن درجة الحرارة العظمى Tmax التي تحدد انتهاء التفاعل بين العناصر الداخلة بتركيب المزيج تزداد بزيادة نسبة هذه المادة . تظهر النتائج أيضاً أن درجة حرارة تسخين (وسط التجربة) تعطي التأثير نفسه الذي تبديه المادة البادئة للتفاعل، وأن المعلومات التي يمكن الحصول عليها تساعدنا في عملية الإنتاج التكنولوجي. أظهرت التجارب أن المالئات العضوية لديها قيم مختلفة لدرجة الحموضة PH وهذا الاختلاف ليس لديه تأثير واضح على منحنيات التصلب، وأن نسبة المالئ العضوي تبدي تأثيرات مختلفة على هذه المنحنيات، ومن الضروري دراسة كل نوع بشكل مستقل The aim of this paper is to study the effect of temperature and PH value of the organic fillers, which are prepared from different kinds of grass, and filler percentage on the hardening curve of the unsaturated polyester resin. The results show that the benzoyl peroxide, which is used like initiator, strongly affects on the the curve behavior and Tmax, which define the finishing of reaction between compenents (unsaturated polyester resin + styrol + benzoyl peroxide), icreases by increasing percentage of benzoyl peroxide. The results also show that the temperature of heating gives an effect similar to that of the initiator, and the information which we obtains from these curves help us in the technology production. the experiments show that the organic fillers have different PH value, and this difference doesn’t have a clear effect on the hardening curves, and the percentage of organic filler shows different effect on the these curves, this is why it is necessery to study evrey kind independently.